A therapeutic update on PARP inhibitors: implications in the treatment of glioma. Issue 2 (February 2021) - Lal, Samridhi; Snape, Timothy J.
Abstract : Central nervous system (CNS) cancers are among the most aggressive and devastating. Further, due to unavailability of neuro-oncologists and neurosurgeons, the specialized treatment options of CNS cancers are still not completely available in most parts of the world. Among various strategies of inducing death in cancer cells, inhibition of poly(ADP-ribose) polymerase (PARP) has emerged as a beneficial therapy when combined with other anticancer agents. In this review, we provide a detailed therapeutic update of PARP inhibitors that have shown clinical activity against glioma. Highlights: PARP inhibitors could improve the overall efficacy of chemotherapy Implications of PARP inhibition in the treatment of glioma is discussed An insight of natural and synthetic PARP inhibitors active against glioma is given